Lecturer Perceptions of Student Competence in Communicating during Teaching and Learning (Case Study at the Faculty of Social and Political Affairs, Gajah Putih University, Takengon) - Suknah (PT FORMOSA CENDEKIA GLOBAL, 2022)
Lecturers' Perceptions of Student Competence in Communicating During Teaching and Learning